A LITERATURE REVIEW AND BIBLIOMETRIC-ANALYSIS OF THE GAME OF BASKETBALL: A CASE STUDY ON INDONESIA AND MALAYSIA - Khairul Hafezad Abdullah; Davi Sofyan; Mohd Firdaus Roslan; Ibraheem Musa Oluwatoyin; Ejiro Uriri Osiobe (Universitas Majalengka, 2022)
This study examines basketball-related trends and publications in Indonesia and Malaysia. The Scopus database yielded 85 papers for this investigation. The analysis is based on four fundamental factors: the distribution of publications, the distribution of scientific sources, the most prolific author, and keywords. Based on our analysis, it is forecasted that publication in this field will increase between 2020 – 2022. The frequent keywords were